Oxygen plasma induced hydrophilicity of Parylene-C thin films - Trantidou,T; Prodromakis,T; Toumazou,C (Applied Surface Science, 2012)
This paper investigates the surface modification of Parylene-C thin films under various oxygen plasma treatment conditions, such as power intensity (50:400 W) and exposure time (1:20 min). The extent of hydrophilicity was investigated through contact angle measurements, and correlations between treatment parameters, film thickness, restoration of hydrophobicity and etching rates were experimentally established. We also demonstrate the selective modification of Parylene-C films, facilitating distinct hydrophilic and hydrophobic areas with μm-resolution that can be exploited in self-alignment applications.